2022
DOI: 10.1016/j.jcot.2021.101744
|View full text |Cite
|
Sign up to set email alerts
|

What is the clinically significant ideal mesenchymal stromal cell count in the management of osteoarthritis of the knee? – Meta-analysis of randomized controlled trials

Abstract: What is the clinically significant ideal mesenchymal stromal cell count in the management of osteoarthritis of the knee? -Meta-analysis of randomised controlled trials

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…Here in, 14 studies including 564 patients were analysed and it was determined that the range of cell dose with the most therapeutic effect was 5-7×10 7 MSCs. 81 The lack of standardization among clinical trials contributes to the varying results of therapeutic efficacy of stem cell treatment for OA. It has been recommended that dose-escalation clinical trials be conducted to better standardize the use of stem cells in the treatment of OA.…”
Section: Cell Therapies For Cartilage Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Here in, 14 studies including 564 patients were analysed and it was determined that the range of cell dose with the most therapeutic effect was 5-7×10 7 MSCs. 81 The lack of standardization among clinical trials contributes to the varying results of therapeutic efficacy of stem cell treatment for OA. It has been recommended that dose-escalation clinical trials be conducted to better standardize the use of stem cells in the treatment of OA.…”
Section: Cell Therapies For Cartilage Regenerationmentioning
confidence: 99%
“…It has been recommended that dose-escalation clinical trials be conducted to better standardize the use of stem cells in the treatment of OA. 81 …”
Section: Cell Therapies For Cartilage Regenerationmentioning
confidence: 99%
“…Table 1 summarizes systematic reviews and meta-analyses on the clinical efficacy of intraarticular injections of MSCs in knee OA [ 19 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ].…”
Section: Efficacy Of Intraarticular Mscs Injections In Knee Osteoarth...mentioning
confidence: 99%
“…An analysis of clinical trials with intravenous administrated MSCs between 2004 and 2018, which reported positive outcomes, indicated minimal effective doses ranging from 70 to 190 million MSCs [ 18 ]. The MSC count in the management of knee osteoarthritis is slightly lower; in the meta-analysis of results of clinical trials, the group of patients with 50–100 million MSCs delivered to the target site showed significant improvement in pain and functional outcomes, while a higher dose was less effective [ 19 ]. Multiple administrations of MSCs with up to several hundred million cells are needed for certain patients and diseases to achieve the desired therapeutic effect [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%